Porous V2O5/TiO2nanoheterostructure films with enhanced visible-light photocatalytic performance prepared by the sparking method - Porntipa Pooseekheaw (2020)
© 2020 by the authors. Porous V2O5/TiO2 nanoheterostructure films with different atomic ratios of Ti/V (4:1, 2:1, 1:1, and 1:2) were synthesized by a sparking method for the first time. The sparking method, which is a simple and cost-effective process, can synthesize highly porous and composite films in one step. Field-emission scanning electron microscope (FE-SEM) images revealed the porosity morphology of all prepared samples. V2O5/TiO2 nanoheterostructure films were confirmed by Raman spectroscopy, high-resolution transmission electron microscopy (HRTEM), and X-ray photoelectron spectroscopy (XPS). The secondary particle size and band gap of the samples were highly correlated to the V2O5 proportion, resulting in enhanced visible-light absorbance. V2O5/TiO2 nanoheterostructure films at an atomic ratio of 1:1 showed the highest photocatalytic performance, which improved the degradation rate up to 24% compared to pure TiO2 film. It is believed that the formed nanoheterostructure and greater portion of V4+ ions are reflected by this ratio.